La representación artística del cuerpo como ideal de belleza (2004)
ABSTRACT: The artistic representation of the body, more than something of his evident and natural one, constitutes all a conquest within the art and the western thought. In fact, the aesthetic thesis of the Kantian one raises that solely a beauty ideal can settle down, from human the corporal figure, in as much this one, is suitable for the expression of the moral, constitutes a conclusive test of the first affirmation. The works of the historian of the Prehistoric Art and old, Sigfried Geidion, and made by Keneth the Clark, equip this thesis with artistic and cultural testimonies, that allow him to surpass their apparent speculative character. This approach to the artistic representation of the aesthetic body from the philosophical one, and the historiography of the art, is pertinent for the debate around the representations of the body. The Kantian thesis on human the corporal figure like beauty ideal makes a different glance around problematic happiness possible